Acoustic Control through Gradient Coil Design Using a Finite-Difference-Based Method for MRI - Liyi Kang; Ling Xia (Discrete Dynamics in Nature and Society)
An acoustic control scheme is proposed in this paper through the process of gradient coil design for magnetic resonance imaging (MRI). With a finite-difference-based method, the stream function and coil displacement caused by fast gradient switching can be unified by a simplified momentum equation, which can be incorporated into the conventional gradient coil design. A three-dimensional transverse gradient coil with an edge-connected cylindrical structure is used as a design example to verify the proposed design method. In addition, an acoustic model is established to simulate the sound pressure level (SPL).In the model, two hemispherical air volumes are added flush with the ends of the cylindrical main magnet to mimic the free propagation of sound waves on the boundaries. The simulation results show that by optimizing coil displacement, the overall SPL can be attenuated by 4 dB over the frequency range from 0 to 3000 Hz with the displacement reduced by about 50%, at the cost of a figure of merit (FOM) loss by about 8%. Therefore, the proposed acoustic control scheme can be used as a complement to conventional acoustic control methods for further noise reduction.